PHYSICAL FITNESS RELATED TO THE HEALTH OF GIRLS AGING BETWEEN 8 AND 11 YEARS OLD (Fiep Bulletin - online, 2014)
The habitual exercise and the sports practice increase the physical performance leading to an improvement of the body functional efficiency. The physical activity practice exerts influence and is influenced by the indexes of physical fitness which determine and are determined by the health condition. In children and adolescents the levels of physical fitness must not be faced only as results of prior experiences but also as an element of promotion of future life styles. Objective: To analyze Physical Fitness Related to Health (PFRH) in girls aging between 8 and 11 years old of a local school of the city of Santa Maria -RS. Methodology: The Study Group has been composed of 51 female students aging between 8 and 11 years old. For the analysis and collection of the PFRH variables, tests and protocols suggested by the AAPHERD (1988) have been applied. Descriptive statistics was used for the data analysis. Results: The girls have presented an age of 10 years old in average, BMI of 18  3 kg/m², SF of 33  12 mm, 23  6 cm in the flexibility test, and 26  7 e 3  2 repetitions in the abdominal test and of bar, respectively. The results were shown to be preoccupying, mainly regarding to muscular resistance and flexibility, where most of the students have presented low scores in relation to the minimum limits of the healthy zones of fitness related to the health. Conclusion: Due to the unsatisfactory scores regarding the components of muscular resistance and flexibility, one can verify that the study group is exposed to postural and articulation problems, muscle-skeletal harms, osteoporosis, lombalgy, and located fatigues.
Keywords: PFRH; girls; health